The Need for Interactive PjBL E-Worksheets in Deep Learning of Flat Shapes Material for 4th Grade Elementary School - Heryanto, Debi; Agusdianita, Neza; Lencana, Destri; Zahrani, Luthfiati (The Future of Education Journal, 2025)
Given the lack of variety in existing learning instruments and the high level of student interest in digital learning, the objective of this study was to describe the needs for developing an interactive electronic Student Workshee that is both relevant to student requirements and aligned with the principles of Project-Based Learning (PjBL) to support deep learning. The methodology employed was quantitative descriptive research, involving 25 students and two teachers from SD Negeri 42 Bengkulu City, who participated through questionnaires and interviews. The results indicate that the majority of students responded positively to the use of E-Worksheets in the teaching and learning process, with 20 students stating that the problems within the E-Worksheets fostered their enthusiasm. Despite this positive sentiment, the data also highlighted the necessity for improving the variety of E-Worksheets content to better match student proficiency. The implication of this research is that the development of the e- E-Worksheets can enhance student engagement, facilitate more profound learning, and prepare students for future academic challenges by integrating active learning methods with modern technology. Thus, the development of PjBL-based E-Worksheets is expected not only to improve academic outcomes but also to build a sustained love for learning among students.